Primary extraskeletal Ewing's sarcoma of the breast in a 13-year-old girl: a case report - Liu, Xiaoge; Li, Xin; Zhou, Chaoxin; Liu, Dan (Frontiers in Pediatrics, 2025)
BackgroundThe Ewing sarcoma family of tumors (ESFT) comprises classic Ewing sarcoma (ES) of the bone and extraskeletal Ewing sarcoma (EES). EES typically arises in the soft tissues of the trunk and extremities. Primary breast ES is a rare entity, predominantly reported as clinical case reports. Furthermore, pediatric primary breast ES is exceptionally rare. To date, there have been few reports of clinical cases.Case presentationwe report a rare case of primary breast ES in a 13-year-old girl from a Chinese ethnic minority group.She presented with an accidentally discovered enlarging mass in her right breast. Initial evaluations at a local hospital, including breast ultrasound and chest CT scan, revealed an 11.8 × 10.3 × 8.5 cm solid and cystic mass within the right breast.This was initially misdiagnosed as a fibroadenoma or a phyllodes tumor, likely due to her younger age. Laboratory findings showed elevated levels of lactate dehydrogenase (LDH) and alkaline phosphatase (ALP). No other extra-skeletal or skeletal lesions were found. Although the patient underwent surgical resection at the local hospital, the inability to obtain definitive histopathological results—owing to limited local medical resources and geographical constraints-precluded the administration of adjuvant therapy. Unfortunately, recurrence was observed just three months postoperatively. Subsequently, in our institution, the definitive diagnosis of primary breast ES was established through immunohistochemical analysis and fluorescence in situ hybridization (FISH). Despite receiving standard chemotherapy and radiotherapy for ES, the patient experienced repeated local recurrences and widespread bone metastases 15 months after her initial diagnosis, ultimately passing away 18 months post-diagnosis.ConclusionPrimary breast ES represents a rare and aggressive malignancy in children. Early discovery, diagnosis, and treatment are crucial for improving survival rates and life quality for these patients.US, CT, and MRI can facilitate clinical diagnosis and preoperative evaluation. This case highlights the necessity of enhancing clinicians and radiologists awareness about this uncommon condition, especially in pediatric patients and in under-served regions.